Brazil: Agricultural R&D indicators factsheet - Flaherty, Kathleen; Guiducci, Rosana do Carmo Nascimento; Torres, Danielle Alencar Parente; Vedovoto, Graciela Luzia; Dias Ávila, Antônio Flávio; Perez, Sandra (International Food Policy Research Institute, 2016)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also feature a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.